Pengaruh Likuiditas, Profitabilitas dan Leverage terhadap Nilai Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonedia (BEI) Periode 2021-2024 - Nurul Jannah; Sigit Pranomo Hadi; Mohammad Chaidir (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of liquidity, profitability, and leverage on firm value, both partially and simultaneously, in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX). Firm value is an important indicator for stakeholders because it reflects investor perceptions of a company’s overall performance and future prospects. Liquidity, as the company’s ability to meet short-term obligations, profitability, as its capacity to generate net income from operational activities, and leverage, as the extent of debt utilization in financing, are fundamental financial factors that can influence how investors assess firm value. The research adopts a quantitative approach with secondary data derived from annual financial statements of companies within the consumer non-cyclicals sector during the 2021–2024 period. Multiple linear regression analysis was employed along with classical assumption tests to ensure model validity, and both partial and simultaneous tests were conducted to examine the hypotheses. The empirical findings reveal that liquidity, profitability, and leverage each have a positive and significant effect on firm value when tested partially, indicating that improvements in these financial indicators contribute directly to increasing firm value. Moreover, the simultaneous testing confirms that the three variables together exert a significant influence, underscoring the importance of a comprehensive financial management strategy. These results highlight that optimal management of liquidity to maintain financial flexibility, maximization of profitability through efficient operations, and prudent use of leverage to balance risks and returns can enhance investor confidence, strengthen competitive positioning, and ultimately increase firm value. The study provides practical implications for managers in formulating strategies that integrate financial policies holistically, as well as for investors in evaluating companies based on their financial structure and performance sustainability.